Biological Activities of Heteropyxis natalensis Against Micro-Organisms Involved in Oral Infections - Henley-Smith, Cynthia J.; Botha, Francien S.; Hussein, Ahmed A.; Nkomo, Mpumelelo; Meyer, Debra; Lall, Namrita (Frontiers in Pharmacology, 2018)
The use of complementary and alternative medicine from plants in South Africa, as in the rest of the world, continues to increase. Heteropyxis natalensis, known as the Lavender tree, is indigenous to South Africa and is traditionally used for oral care. The ethanolic extract, of the leaves and twigs, of H. natalensis was investigated for antimicrobial activity against selected oral microorganisms. Actinomyces israelii was found to be the most sensitive oral microorganism to the extract, with a minimum inhibitory concentration (MIC) of 0.88 mg/ml and an MIC of 2.6 mg/ml against Streptococcus mutans. Five known compounds were identified from the ethanolic extract of H. natalensis. The compounds were identified as aurentiacin A (1), cardamomin (2), 5-hydroxy-7-methoxy-6-methylflavanone (3), quercetin (4) and 3,5,7-trihydroxyflavan (5). The MICs of the compounds 1 and 4 were found to be 0.06 mg/ml and 1 mg/ml, respectively, against A. israelii. The cytotoxicity, acute and sub-acute toxicity in pre-clinical studies were also determined for H. natalensis. The extract showed moderate cytotoxicity (35.56 ± 0.16 μg/ml) on human monocyte cells. The acute and sub-acute toxicity analysis of H. natalensis indicated the NOEL (no-observed-effect level) at 200 mg/kg. Interleukin-8 (IL-8) is a chemokine that stimulates the recruitment of leukocytes. A significant reduction of IL-8 production by macrophage cells was observed when exposed to the extract of H. natalensis. It is possible that H. natalensis can prevent excessive tissue damage in periodontal diseases through its reduction of inflammation. Enzymatic bioanalysis of lactic and acetic acid production from Streptococcus mutans and Lactobacillus paracasei was done. A reduction in the acid production from each bacterium was observed on exposure to the extract of H. natalensis. Consequently, this increased the pH, which could possibly reduce the demineralization of enamel which may help prevent the formation of dental caries. In addition the extract may be considered for preventing periodontal diseases.